Earnings Quality in the IFRS Era: Evidence from Morocco - Oubahou Yassine; Elouafa Khalid; Wali Senda (Qubahan Academic Journal)
Purpose: the aim of this study is to determine whether the introduction of International Financial Reporting Standards (IFRS) by Moroccan companies listed on the Casablanca Stock Exchange will contribute to improving the quality of earnings. Methodology: This study spans six years (2015-2020) and a sample of 27 listed Moroccan groups. Furthermore, we divided earnings quality into two main dimensions: on the one hand, earnings management, measured by earnings smoothing and earnings management towards small positive amounts; on the other hand, earnings attribute quality, assessed by accruals quality, persistence and predictability of net income and operating cash flows. Findings: The results of the empirical tests can be divided into two categories: On the one hand, the results of tests of the effect of IFRS on earnings management practices as the first measure of earnings quality show that companies use earnings management in the post-IFRS period compared with the pre-IFRS period. Furthermore, the results of tests of the effect of IFRS on the quality of earnings attributes as a second measure of earnings quality show that the various measures used appear to be of better quality in the pre-IFRS period than in the post-IFRS period. This indicates that the adoption of IFRS in the Moroccan context is contributing to deterioration in the quality of information. Practical implications: The authors demonstrate that the serious and rigorous adoption of IFRS by preparers, as well as training and seminars on the interpretation and application of each standard, are important to accentuate the positive effect of IFRS on the reliability of results. In addition, the findings provide policy-makers and stakeholders in the Moroccan financial market with an insight into the quality of Moroccan standards compared with IFRS in terms of earnings quality. Originality/value: to the best of the authors' knowledge, studies on the effect of IFRS on earnings quality in the Moroccan context are rare, if not non-existent. We therefore focus on this financial center, which mirrors developing countries, in order to highlight the effects of the introduction of IFRS on this type of market.